2021
DOI: 10.3389/fped.2021.783745
|View full text |Cite
|
Sign up to set email alerts
|

Timely Recognition and Early Multi-Step Antinflammatory Therapy May Prevent ICU Admission of Patients With MIS-C: Proposal for a Severity Score

Abstract: In this observational study, we report the clinical, therapeutics and outcome features of 23 patients with multisystem inflammatory syndrome (MIS-C) who have been treated in Gaslini Children Hospital (Genoa, Italy) with a multistep antinflammatory treatment protocol, based on disease severity at admission. Patients were initially assigned to four severity classes on admission and treated accordingly. The therapeutic options ranged from IV immunoglobulin alone to a combination of IVIG plus pulses of methylpredn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 31 publications
4
37
1
Order By: Relevance
“…Although IVIG is the first preferred one, steroids, and biological drugs such as anakinra and tocilizumab are also among the main treatment options. Steroids may be considered as a treatment option in milder forms, while severe or refractory cases should receive more intensive treatment [ 18 , 19 ]. Accordingly, patients in clusters II and III more commonly required intensive care, pulse steroid, anakinra, and inotropic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although IVIG is the first preferred one, steroids, and biological drugs such as anakinra and tocilizumab are also among the main treatment options. Steroids may be considered as a treatment option in milder forms, while severe or refractory cases should receive more intensive treatment [ 18 , 19 ]. Accordingly, patients in clusters II and III more commonly required intensive care, pulse steroid, anakinra, and inotropic agents.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the good response to steroids might be biological similiarities to toxic shock syndrome, involving the T-cells, as recently described by Sacco et al (24). Furthermore, recently appeared evidence supports early start of anti-inflammatory treatment (25,26). Our patients showed excellent response with improved blood pressure to initial volume administration, immunomodulatory and antiinflammatory treatment.…”
Section: Discussionmentioning
confidence: 83%
“…A review of the CDC MIS-C database 99 identified other factors associated with poor outcomes. Children ˃5 years, black or Hispanic ethnicity, and the presence of thrombocytopenia and lymphopenia were associated with worse outcomes.…”
Section: Resultsmentioning
confidence: 99%